The Influence of Ultra-Processed Food on Childhood Obesity: A Systematic Review - Evie Kusmiati; Erwin Santoso Sugandi; Syahroni Lubis; Intan Masita Hayati; Muhammad Hudzaifah Nasrullah (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Purpose: This study aims to evaluate the impact of ultra-processed food (UPF) consumption on the risk of obesity in children through a systematic review of studies published between 2019 and 2024.Methodology: Using a Systematic Literature Review (SLR) method with the PRISMA approach, this study screened 319 articles from the Scopus database, ultimately selecting 13 relevant articles based on inclusion and exclusion criteria using the PICOC framework.Findings: A significant correlation exists between UPF consumption and childhood obesity risk. UPFs are associated with elevated BMI, increased waist circumference, nutrient deficiency, and addictive eating patterns. Socioeconomic status, educational setting, and advertising exposure exacerbate these adverse outcomes.Research Limitations: The primary constraints encompass methodological discrepancies across the analyzed studies, an absence of longitudinal data, and restricted applicability of findings to developing nations.Practical Implications: These findings endorse the development of evidence-based nutrition policies, including food labeling and UPF advertising restrictions for children.Originality: This research introduces a novel